Information Mastery, Effective Health Care, Evidence-Based Practice and the Otolaryngologist - Deepa Bhargava; Yousef Al-Saidi; Kamlesh Bhargava; Rashid Al-Abri (Sultan Qaboos University Medical Journal, 2011)
Objectives: The objectives of this study were to study the information-seeking behaviour of otolaryngologists in Oman, and their willingness to learn and acquire evidence-based practice (EBP) skills. Methods: A cross-sectional survey was carried out by distribution of a questionnaire to 63 otolaryngologists (ranging from residents to consultants) employed in Oman who attended a national otolaryngology meeting in January 2010. Results: Forty-nine completed questionnaires were received; 57% of the respondents had more than 10 years’ experience, and 60% were from tertiary care; 38.8% “totally agreed”, and 36.7% “partially agreed” that EBP would improve the quality of care and thus provide effective health care to patients. More than 46.9% had 1–5 questions per week, 18.4% had 11 or more questions per week at the point-of-care; 69.4% were willing to acquire information mastery skills. There was a statistical correlation between the number of years of experience, the number of questions, and willingness to acquire information mastery skills. Conclusion: In day-to-day clinical practice, web-based resources are of increasing significance. Most otolaryngologists in Oman not only believed that it is essential to acquire information mastery skills, but also that effective health care depends on such skills and on EBP. Most were willing to acquire these skills. In the future, these skills will be vital in helping otolaryngologists deliver effective health care solutions.